Pengaruh penggunaan teknologi dalam pembelajaran matematika terhadap prestasi siswa - Maghfiroh, Alifia Nisa (Maliki Interdisciplinary Journal, 2024)
Math learning is now more interactive and engaging thanks to technologies such as educational apps, hardware (such as computers and tablets), and e-learning platforms. Studies show that technology can improve students’ understanding of math concepts and their learning outcomes. However, the application of technology in math education also faces challenges, such as lack of access to devices and the internet and lack of teacher instruction. In this article, various technologies used in math learning are identified, looking at how they affect student performance, and looking at what makes them effective. The results show that while technology has great potential to improve math learning, digital shortages and the need for teachers to get adequate training are the main obstacles to overcome. This article provides practical suggestions for educators and policymakers on how to optimize the use of technology in mathematics education. These recommendations include the importance of providing training to teachers, ensuring all students have equal access to technology and integrating technology into the curriculum. Thus, technology can be used effectively to improve student achievement in mathematics.